Measuring student satisfaction towards mobile service provider in Bangladesh: with special reference to Grameen phone limited - Kumar, Dhanonjoy; Mukherjee, Subhadeep; Haque, A. K. M. Ahasanul; Anis, Zohurul (Science Press, 2020)
Customer satisfaction is an important word that commonly uses in marketing. It is a proportion of how products and services provided by an organization meet or enhance client desires. This research work looks to examine student fulfillment and its impacting variable of the cell phone industry in Bangladesh. This research work is led to 320 Grameenphone (GP) clients in Bangladesh. Over the span of data analysis, recurrence rate, bar graphs, the trial of unwavering quality, KMO-Bartlett test, exploratory factor investigation, correlation, and linear regression investigation have been utilized. The outcome shows that a noteworthy relationship exists between consumer loyalty and service quality, network, call rate, web facility, and social duty. The outcome likewise shows that all these services are noteworthy indicators of consumer loyalty. Present research work concluded that the satisfaction level of students of Grameenphone constrained isn't sufficient.